2017
DOI: 10.1038/nrendo.2017.173
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease and chronic vascular complications of diabetes mellitus

Abstract: Nonalcoholic fatty liver disease (NAFLD) and diabetes mellitus are common diseases that often coexist and might act synergistically to increase the risk of hepatic and extra-hepatic clinical outcomes. NAFLD affects up to 70-80% of patients with type 2 diabetes mellitus and up to 30-40% of adults with type 1 diabetes mellitus. The coexistence of NAFLD and diabetes mellitus increases the risk of developing not only the more severe forms of NAFLD but also chronic vascular complications of diabetes mellitus. Indee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
238
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(260 citation statements)
references
References 196 publications
(234 reference statements)
10
238
1
11
Order By: Relevance
“…Over the next 20 years, NASH in T2DM is projected to account for 29% of all liver transplants and 812,000 liver‐related deaths. Of note, the model did not include the potentially higher rates of diabetes‐related micro‐ and macrovascular complications associated with NASH . These findings should alarm diabetologists and prompt them to become proactive by viewing NASH as a common and serious complication of T2DM that should be systematically screened …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the next 20 years, NASH in T2DM is projected to account for 29% of all liver transplants and 812,000 liver‐related deaths. Of note, the model did not include the potentially higher rates of diabetes‐related micro‐ and macrovascular complications associated with NASH . These findings should alarm diabetologists and prompt them to become proactive by viewing NASH as a common and serious complication of T2DM that should be systematically screened …”
mentioning
confidence: 99%
“…Of note, the model did not include the potentially higher rates of diabetes-related micro-and macrovascular complications associated with NASH. 5 These findings should alarm diabetologists and prompt them to become proactive by viewing NASH as a common and serious complication of T2DM that should be systematically screened. 6 A step forward in the field of diabetes has been the 2019 Standard of Care guidelines by the American Diabetes Association that recommended that "patients with T2DM and elevated liver enzymes aminotransferase (ALT) or fatty liver on ultrasound should be evaluated for the presence of NASH and liver fibrosis" (Recommendation 4.14, page S40).…”
mentioning
confidence: 99%
“…2 In addition, common genetic variations in the membrane-bound O-acyltransferase domain-containing 7 (MBOAT7) and in the transmembrane 6 superfamily member 2 (TM6SF2) genes have also been associated with increased susceptibility to NAFLD and its severity. 5 Nondiabetic endocrinopathies are also increasingly being linked to fatty liver. 4 NAFLD has also been reported in up to 80% of patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a serious health threat which can adversely affect multiple organs due to its long‐term complications . The mortality from cardiovascular complications in the diabetic population is approximately three to five folds higher than the general population . It has been reported that risk factors in diabetes, including insulin resistance, impairment of insulin‐induced whole‐body glucose uptake, dyslipidemia, and atherosclerosis induced oxidative stress could impair the endothelial function.…”
Section: Introductionmentioning
confidence: 99%